Corporate Social Responsibility (CSR) dan Tax Avoidance: Bukti Empiris dari Perusahaan Manufaktur di Indonesia - Wahyuningsih, Wahyuningsih; Zenabia, Tsarina (Journal of Economics, Bussiness and Management Issues, 2025)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) and sales growth on tax avoidance in manufacturing companies in the food and beverage sector for the period 2019–2023. This research employs a quantitative approach with purposive sampling. Data processing is conducted using E-Views 12 with a multiple linear regression model. Classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests, indicate that the data meet the necessary analytical requirements. The findings reveal that CSR has a significant effect on tax avoidance, while sales growth does not significantly influence tax avoidance. Simultaneously, CSR and sales growth collectively affect tax avoidance. The coefficient of determination is 54.49%, indicating that the independent variables explain this proportion of the variation in tax avoidance, while the remaining 45.51% is influenced by other factors outside the model. These findings highlight the crucial role of CSR in corporate tax avoidance practices, whereas sales growth does not directly impact the level of tax avoidance.